Notes for an Intellectual History of the Friedrich-Ebert-Stiftung in Latin America (1964-1989) - Garategaray, Martina (2024)
The promotion of democracy was from its origins one of the banners of the Friedrich Ebert Foundation (FES), ideologically linked to the German Social Democratic Party (SPD) and which disembarked in Latin America in the 1960s. It is this transnationalization that we are interested in exploring from the perspective of intellectual history (Altamirano, 2005, Palti, 2004-2005), breaking with a unidirectional idea of transfers and circulations, in order to understand the exchange and connections between regions, ideas and people. The article first focuses on explaining the particularity of the German Political Foundations and the functioning of the FES in Latin America and then goes on to explore three intellectual projects of the Foundation, such as the Latin American Institutes for Social Science Research (ILDIS), the Center for Democratic Studies of Latin America (CEDAL) and the New Society Journal (NUSO). Based on the premise that ideas are important insofar as they conveyed meanings and representations in the region, this paper seeks to map the little known but strong presence of the FES in Latin America during the Cold War years. And how it became an important platform capable of connecting people, ideas and regions. In this framework, the FES, and this is our bet, can be thought of as an intellectual network that, while participating in and promoting debates on development, dependence, anti-imperialism, revolution and democracy, was building a space for indigenous social democracy.